Investigations of tissue folates in normal and malignant tissues. - Pheasant, A. E. (Nature Publishing Group, 1983)
The folates present in liver, gut and tumour tissue were examined before and after autolysis. Before autolysis 10-formylfolate tetraglutamate (10-CHOFA(glu)4), 5-methyltetrahydrofolate triglutamate (5-CH3THF(glu)3) and possibly tetrahydrofolate polyglutamate(s) (THF(glu)n) were detected. Liver contained all 3 species whereas no 5-CH3THF(glu)3 was present in the tumours; gut showed an intermediate situation. After autolysis the predominant monoglutamates formed were 5-CH3THF in the liver, 10-formylfolates in the gut and possibly tetrahydrofolate (THF) in the tumour extracts. These differences illustrate changes in tissue folates with the proliferation rate of the tissue and suggest an explanation for the methionine auxotrophy of Walker 256 carcinosarcoma cells.